Perbedaan Status Gizi Bayi Umur 0-6 Bulan Antara Bayi yang Mendapatkan ASI Dengan Bayi yang Mendapatkan ASI dan Susu Formula di Kelurahan Dukuh Sidomukti Kotamadya Salatiga - Purwaniati, Agustina Kristiani; , Ir. Listyani Hidayati, M.Kes; , Fitriana Mustikaningrum, S.Gz, M.Sc (2013)
Introduction: Exclusive breast-feeding is a process of breast. Feeding in infants during the first 6 months without additional mixed with liquid and solid food. Monitoring nutritional status in 2012 in Dukuh district , data obtained that 1,4%infants have more nutritional status, 93,6% good nutritional status, 4,48% less nutritional status, and 0,56% severe malnutrition. Coverage of exclusive breast. Feeding in infants aged 0-6 months in Dukuh district decreased by 2% in 2012. Objective:Knowing the difference in the nutritional status of infants aged 0-6 months among infants who received breast milk to infants who received breast milk and formula milk in Dukuh district, Sidomukti subdistrict, Salatiga. Research Method : The type of research is an analytic survey with cross sectional approach. Population consisted of 2 (two) groups of the population, thay are the population of infants aged 0-6 months who received breast milk of pre-lactate total 31 babies and infants population aged 0-6 months who received breast plus formula milk total 32 babies. Test the differenece with Independent sample t Test. Results : Nutritional status of infants aged 0-6 months who received breast milk as such as 83,87% good nutritional status, 12,90% less nutritional status, 3,23%more nutritional status, with an average value of Z-score SD -0,9361 while the nutritional status of infants aged 0-6 months who received breast milk plus milk formula 100% is good nutritional status with an average value of Z-score SD two groups of babies is almost the same, so the two groups of infants mostly had good nutritional status (p=0,351 > 0,05) Conclusion : There was no difference in the nutritional status of infants aged 0- 6 months who received breast milk to infants who received breast milk plus formula milk in Dukuh district, Sidomukti subdistrict, Salatiga.